Cross-sectional associations between number and ages of children and maternal physical activity. (20th October 2021) - Simpson, RF; Hesketh, KR; Crozier, SR; Baird, J; Cooper, C; Godfrey, KM; Harvey, NC; Westgate, K; Inskip, HM; van Sluijs, EMF
Abstract: Background: Physical activity (PA) has many health benefits, but parenthood is often associated with reduced PA in mothers. Determinants of adult PA are diverse, but ages and number of children may be key factors linked to maternal PA. Few studies have compared PA levels of mothers of school-aged children with those who have younger children, which is vital considering that maternal PA patterns may change at transition to formal schooling. Studies using device-assessment to investigate this association are also sparse. We aimed to investigate the association between number and ages of children and maternal device-measured moderate-to-vigorous PA (MVPA). Methods: Cross-sectional analyses were conducted using data from 848 mothers from the Southampton Women's Survey when the index child was 4 or 6-7 years old. Two-level random intercept linear models were run to investigate associations between self-reported number (1, 2, 3+) and ages (4y and under, 5y and over, both age groups) of children, and their potential interaction, and accelerometer-assessed log-transformed minutes of maternal MVPA. Results are presented as % difference in minutes of MVPA. Results: 41% of mothers met PA guidelines (150 minutes of MVPA/week). Women who had any children 5y and over engaged in more MVPA than those with only children 4y and under (e.g. % difference in minutes of MVPA: 42.2, 95% CI 18.7 to 70.4 for mothers with only children 5y and over vs those with only children 4y and under). Mothers with 2 or 3+ children did less MVPA than those with 1 child (e.g. 13.9, 1.0 to 25.2 less MVPA for women with 2 children vs those with 1 child). Conclusions: Mothers with multiple children or any children 4y and under do less MVPA than those with 1 child or only school-aged children. Interventions and policies are needed to support these mothers to increase their time spent doing MVPA, especially considering the additional health benefits associated with this level of intensity of PA. Key messages: Most mothers are insufficiently physically active to gain the associated health benefits. Interventions to increase MVPA particularly need to target mothers of younger children and those with multiple children.